Ear Acupuncture Points in Neonates From Drug-Dependent Mothers: A Prospective Study - Stähler van Amerongen, Kirsten; Kuhn, Annette; Surbek, Daniel; Nelle, Mathias (Frontiers in Pediatrics, 2021)
Aim of the study was to determine the presence of ear acupuncture points (EAP) in neonates with or without neonatal abstinence syndrome (NAS) and to confirm the hypothesis that sick neonates have more EAP than healthy neonates. Methods: A prospective case control study with ethical consent at the University Children`s Hospital, Division of Neonatology and the Department of Gynaecology and Obstetrics Inselspital Bern in Switzerland. We examined 26 newborns of drug dependent mothers determining their EAP as compared to 50 healthy newborns. Results: 26 neonates with NAS were screened. 24 EAP could be detected on the left and 25 on the right ear lobe. There was no significant difference between the right and left lobe (p = 0.9285, two tailed test) and the number of EAP. The most common point was the psycho-vegetative rim. Organic points, the pain point Shenmen and NADA points were found. Correlation between gender and active ear points was highly significant (p = 0.0093, Mann Whitney Test for the left lobe and p=0.0025 for the right lobe). Male neonates demonstrated a significantly higher number of active ear points. The correlation between the Finnegan Score and the number of ear acupuncture points was highly significant (p= 0.0001). The results of newborns from drug abusing mothers were compared with the results from 50 healthy neonates and showed that newborns of drug dependent mothers had statistically significant more active points than those of controls. The difference between the left ear lobe of neonates of drug-dependent mothers compared with those of the controls were statistically significant (p = 0.0008, Mann Whitney test). Very similar results were found concerning the right ear lobe (p = 0.0001, Mann Whitney Test). Discussion: Our current work confirms that sick neonates from drug abusing mothers with high points of Finnegan score and NAS have more AEP than healthy neonates. The vegetative rim is the most common point.. Newborn male had a higher number of AEP than female. Possibly, EAP in neonates could be used for diagnosis and therapeutic opinions in the future. The study was approved by the ethics committee of Bern, Switzerland (KEK Nr.142/02).